Editorial: English/Inglês - Mota, Editor, Maurício (REVISTA QUAESTIO IURIS, 2015)
DOI: http://dx.doi.org/10.12957/rqi.2015.16977 The Journal Quaestio Iuris in this volume 08, number 02, the second number of the year 2015, has the great pleasure to inform all readers and friends that now, in June 2015, CAPES, Foundation linked to Ministry of Education, through its Committee Qualis Periodicals, ranked our magazine as A2, Law! This is an extraordinary result that makes us all very happy and imposes a huge responsibility of producing an even better legal magazine for our readership in the areas of philosophy of law, legal theory, Legal Dogmatic, History of Law, and Sociology of Law.